Guairea milleri nov. gen. et sp. y Guaireaceae, nueva Familia de las Osmundales (sensu lato) del Pérmico Superior de Paraguay (Ameghiniana, 2013)
"A new Osmundaceous fern with a remarkable structure from the Upper Permian of Paraguay is described. It was necessary to create a new genus and species, Guairea milleri. Also a previously known species, Osmundacaulis carnieri (Schuster) Miller, is referred to this new genus. The anatomical characters of both species of Guairea required the erection of a new Family as well, which distinctive characters are: a) The stele is an ectophloic dictyostele: it has pericycle and phloem externally only, but endodermis completely surrounding each meristele. b) Complete absence of sclerenchymatic sheaths and stipular expansions in the petioles (and leaf traces). c) The cortex is homogeneous and arenchymatic: there is no distinction between internaland external cortexes. d) The leaf-trace formation is by ""invasion"" and centrifugal development of the endodermisin the internal sinuses of the meristeles, and the formation of inmediate leaf-gaps. e) The xylem cylinder is very thick (55-65 tracheids) and definitively arborescent in habit. In the general discussion the set of characters which differentiates the Guaireaceae from therest of the known Osmundales, and justifies the creation of a new Family in the Order, with which it shares the general architecture, is analized. An attempt is made to reconcile the sum of anatomical characters of Guairea with the (elsewhere) proposed evolutionary sequence of the Osmundales, but due to the scarcity of Southern Hemisphere representatives it is premature to try to establish phylogenetic relationships. In any case, the Guaireaceae represent early specialized members of the Order."